Synthesis and characterization of a new series of Dithiocarbazato schiff bases and their transition metal complexes - Rusli, Aqilah Fasihah (2015)
The research described in this thesis focuses on the synthesis and characterization of four new Schiff butyl- (or hexyl-) S-substituted Schiff bases. S-alkyl-β-N-(p-methoxyphenyl)methylenedithiocarbazate (MSBu/MSHe) and S-alkyl-β-N-(p–nitrophenyl)methylenedithiocarbazate (NSBu/NSHe) formed by condensation reaction of newly synthesized S-butyldithiocarbazate and S-hexyldithiocarbazate, with 4-methoxybenzaldehyde and 4-nitrobenzaldehyde and their transition metal complexes. Complexes of copper(II), nickel(II), zinc(II) and cadmium(II) were synthesized in 2:1 mole ratio (Schiff base: metal) in ethanol. All compounds were characterized using various physico-chemical techniques and spectroscopic methods. Single crystal X-ray analysis was carried out on S-methyl-β-N-(p-methoxyphenyl)methylenedithiocarbazate and its copper (II) and nickel (II) complexes, Cu[MSBu]2 and Ni[MSBu]2 as well as the nickel (II) complex of S-hexyl-β-N-(p-methoxyphenyl)methylenedithiocarbazate, Ni[NSHe]2. The Schiff base MSBu, Ni[MSBu]2 and Ni[NSHe]2 crystallized in the triclinic system with the space group of P -1. Cu[MSBu]2 complex crystallizes in the monoclinic space group P 1 21/c 1. The Cu(II) and Ni(II) complexes are four coordinate with trans square-planar configuration with the Schiff base acting as a bidentate chelating agent coordinated via the azomethine nitrogen and thiolate sulphur atom. Although for Zn(II) and Cd(II) efforts to obtain single crystal were not successful, elemental analyses and spectroscopic data indicate that they also adopt four-coordinated structures.